Effectiveness of the novel teledentistry “HI BOGI” an android-based oral health application in increasing oral health knowledge of elementary school children - Fadilah, Rina Putri Noer; Pribadi, Ari Prayogo; Aji, Rizki Wisnu; Kusaeri, Ramadani (Universitas Padjadjaran, 2021)
Introduction: Knowledge is the domain of behaviour. A person's good oral health behaviour must meet the elements of good oral health knowledge. Lack of oral health knowledge is one of the causes of oral dental disease. The most common oral dental disease, particularly in elementary school, is dental caries. One of the efforts to improve oral health knowledge is to be obtained from health promotion. The COVID-19 pandemic has led to many online health promotion media. One of the health promotion media is an Android-based oral health application. The purpose of this study was to determine the effectiveness of the application of oral health on knowledge of oral health in elementary school children during the COVID-19 pandemic. Methods: Using an observational analytic method with a cross-sectional design. The sampling technique used is simple random sampling. The research instrument is a questionnaire via google form and the HI BOGI application. Analysis of the data used is the Wilcoxon test. Results: The study was conducted on 143 elementary school students in Cimahi City. 55.2% are female, and 36.4% are 12 years old. The level of knowledge of oral health before downloading the HI BOGI application was in the moderate category and became good after downloading the application. There was a significant value of knowledge before and after downloading the HI BOGI application with a significant value p<0,0000. Conclusion: There is an effect of HI BOGI to increase oral health knowledge in elementary school children.